Open‐label study evaluating outpatient urethral sphincter injections of onabotulinumtoxinA to treat women with urinary retention due to a primary disorder of sphincter relaxation (Fowler's syndrome). (8th November 2015) - Panicker, Jalesh N.; Seth, Jai H.; Khan, Shahid; Gonzales, Gwen; Haslam, Collette; Kessler, Thomas M.; Fowler, Clare J.
Abstract : Objectives: To assess the efficacy (defined as improvements in maximum urinary flow rate [ Q max ] of ≥50%, post‐void residual urine volume [PVR] and scores on the International Prostate Symptom Score [IPSS] questionnaire) and safety of urethral sphincter injections of onabotulinumtoxinA in women with a primary disorder of urethral sphincter relaxation, characterised by an elevated urethral pressure profile (UPP) and specific findings at urethral sphincter electromyography (EMG), i.e. Fowler's syndrome. Patients and Methods: In this open‐label pilot Institutional Review Board‐approved study, 10 women with a primary disorder of urethral sphincter relaxation (elevated UPP, sphincter volume, and abnormal EMG) presenting with obstructed voiding (five) or in complete urinary retention (five) were recruited from a single tertiary referral centre. Baseline symptoms were assessed using the IPSS, and Q max and PVR were measured. After 2% lidocaine injection, 100 U of onabotulinumtoxinA was injected into the striated urethral sphincter, divided on either side, under EMG guidance. Patients were reviewed at 1, 4 and 10 weeks after injection, and assessed using the IPSS, Q max and PVR measurements. The UPP was repeated at week 4. Results: The mean (range) patient age was 40 (25–65) years, and the mean symptom scores on the IPSS improved from 25.6 to 14.1, and the mean 'bother' score reduced from 6.1 to 3.5 at week 10. As compared with a baseline mean Q max of 8.12 mL/s in the women who could void, the Q max improved to 15.8 mL/s at week 10. Four of the five women in complete retention could void spontaneously, with a mean Q max of 14.3 mL/s at week 10. The mean PVR decreased from 260 to 89 mL and the mean static UPP improved from 113 cmH2 O at baseline to 90 cmH2 O. No serious side‐effects were reported. Three women with a history of recurrent urinary tract infections developed a urinary tract infection. There were no reports of stress urinary incontinence. Seven of the 10 women opted to return for repeat injections. Conclusions: This pilot study shows an improvement in patient‐reported lower urinary tract symptoms, and the objective parameters of Q max, PVR and UPP, at 10 weeks after urethral sphincter injections of onabotulinumtoxinA. No serious side‐effects were reported. This treatment could represent a safe outpatient treatment for young women in retention due to a primary disorder of urethral sphincter relaxation. However, a larger study is required to confirm the findings of this pilot study.